Archival Nothing - Fiol-Matta, Licia (Current Musicology, 2018)
As opposed to other realms of art, like literature or painting, a plethora of “great women singers” has existed in the Caribbean and Latin America since the recording industry began. These were marquee artists with legions of adoring fans. Yet, the critical paucity regarding their careers has been severe. It seems obvious, but bears repeating, that, at the beginning of the twenty-first century, most music writing on Latin America did not engage in a hermeneutic with regards to gender. As I compiled buried, fragmentary, or discarded archival objects, I came to think of my subjects as not having come into critical view yet, as not yet being “interpretable.” I found in the nothing a highly suggestive concept that allowed me to work productively with absences and omissions, but also to analyze singers as able sculptors of a generative nothingness. Related to both the nothing as empty and, in contradistinction, as empty-set, a paradoxical “full emptiness,” I had to consider the common-sense concept of diva, often employed to account for every instance of female stardom and success (rendering it empty). For this book, I decided to keep my critical stance at a remove from the “diva” while not discounting the term’s everyday and scholarly use, the moments when it indexes the generative nothing (which might be one of its definitions). In The Great Woman Singer, I opted for a deferral of diva in favor of a foregrounding of musician. Were I to categorize my four subjects in diva terms, I would say that, in my study, the most ironic diva is Myrta Silva, surely one of the most brilliant entertainers in Caribbean music history and one who, because of her work, any critic would be hard pressed to put into the service of an exemplary feminine performativity. Her correlate, in terms of a conceptual understanding of artistic distance and crafting of persona, is the preternaturally gifted Lucecita Benítez, who left many listeners “waiting” for her to achieve her seemingly boundless potential and who was, apparently, herself left arrested in waiting, suffering the consequences of over-signification and the pressure to represent too many things to too many listeners. Both are queer divas. In Lacanian terms, the first was extraordinarily attuned to the symbolic functions of music, its relationship to desire and the law; the second was perilously close to the real of music, its takeover by desire and law when the various bars of social life have weakened or broken down. I also write on a black diva and a folk diva. These should be nonsensical formulations, as a diva should not have any markers next to her name qualifying the reason for her hallowed position. The performing, female bodies of Ruth Fernández and Ernestina Reyes were admitted into the local pop pantheon in conditional, highly problematic terms, as what Foucault would call, in a memorable essay, docile bodies. Regardless of whether the individuals were docile, their star bodies sedimented into a local musical typology of racial and class otherness, common across the Latin American musical world in the short twentieth century. As opposed to Silva and Benítez—my gritty lead and volcanic coda—Fernández and Reyes are more closely aligned with an imaginary of racial classifications forged in the heyday of the Commonwealth of Puerto Rico, corresponding to the apotheosis of developmentalism. This does not mean that our listening to them has to be of the order of docility, however, or that we need not acquire tools to listen to Silva and Benítez in tune with their particular artistic calls to their listeners. I start with the mercurially negative Myrta Silva and end with the recalcitrant “National Voice,” Lucecita Benítez, to explore the multiple aspects of vocal performance, positing two racially defined, mandated figures of plenitude, the pedagogue Ruth Fernández and free spirit Ernestina Reyes, as similarly essential to my gender analysis of voice. The search for documentation regarding Silva (chapter 1) and Fernández (chapter 2), two famous pop stars in the 1940s and through careers that spanned decades, was painstaking. Still, it was possible to locate their recordings, read about them in print, and, working imaginatively, find photographs of early performances as well as footage from the 1960s and 1970s. I located associates who deeply respected Silva. Collectors were very fond of her, possibly because she was so connected to Cuban music in the 1940s. In truth, Silva was brilliant, a performer who would not go unnoticed, as I discuss, so a lot of credit must go to her. Fernández, in the meantime, accrued international praise for her 1940s recordings of semi-classical, Afrocubanist music which, as I detail in the chapter, caught the attention of the Metropolitan Opera House. She was also on the collector’s radar, even if not as listened to, perhaps, as Silva. After the 1950s, Fernández became a highly influential politician and symbol of the hegemonic political party, the Popular Democratic Party (Partido Popular Democrático, PPD). Therefore, she was, like Silva, “findable,” albeit with a lot of effort since neither artist had been written about beyond some brief, biographical articles. Patience and persistence paid off, eventually. In a few years, I had enough of an archive to theorize voice in both singers. If reconstructing their career was difficult, it was nothing compared to reconstructing the career of La Calandria (chapter 3), a star of the Puerto Rican working classes and the Puerto Rican diaspora. I was lucky to meet two ideal collaborators in Arturo Butler (a diehard Calandria fan from the Bronx, New York) and Grego Marcano (son of an important musician and music promoter, Piquito Marcano). Had I remained in the confined circles of the library, and only spoken to recognized, traditional collectors with the ritualistic, gendered, reverential codes they expected, I would not have encountered either one. It was only the long, methodical pursuit of contacts in all manner of places and with all kinds of people, recorded in a set of scribbled notebooks with dozens of names, phone numbers, emails, annotated places, events, and facts, that led me to visit their homes. While I obtained a comprehensive archive of recordings by pooling materials from Butler and Marcano, and splendid visuals from Marcano, in this chapter, most of all, I experienced the archival nothing. Most jíbaro musicians and associates I talked to were interested in my book and generous with their time. Still, when I queried sources about Calandria’s music career, her musical temperament, or any aspect that had to do with music, folks did not have very much to say about her music making. How did she select her repertoire? How did she record? (In one sitting, one presumes, given the financial precarity of the music.) Did she improvise, as in the mythology surrounding the décima, or work with lyrics? Did she collaborate for any of the songwriting? And so forth. Neither recordings, interviews, nor print research answered these questions. Recordings have a silent aspect, as Jonathan Sterne has theorized. The musicians who still lived were quite old, so their memory was not necessarily up to par. I found very little of jíbaro music reported on in any print venue, of record or gossip. Jíbaro musicians—the entire group—were not seen as professional musicians in their day, simply because of class prejudice. In archival terms, they have a scant presence in record collections, were rarely filmed or photographed, and were never subjects of newspaper and magazine stories. Regarding gender specifically, people in the jíbaro music world had not given the question much of a thought and they were used to talking about women only in terms of their physical appearance or perceived temperament. Lucecita Benítez, a recipient of the 2017 Latin Grammy for Lifetime Achievement Award, is the subject of chapter 4 and the only living artist I studied. Lucecita began her career in the 1960s with the explosion of consumer culture in Puerto Rico, signifying illusory wealth, and experienced her peak in the 1970s, coinciding with the beginning of developmentalism’s demise. Hundreds of fans acquired records without having to pay too much; saved their copies of Bohemia or TV Guía; clipped the newspapers; held on to flyers or concert programs; and snapped photos of their beloved star. Contact with 1970s and 1980s fans helped me think through the change in music and subjectivity that the primacy of reception inaugurated, as John Mowitt (1987) illustrated in a landmark essay, “The Sound of Music in the Era of its Electronic Reproducibility.” Yet, even Lucecita (a relatively easy object of study compared to the rest, with an abundance of archival material, much of it existing outside of formal, private collections) had not received the critical analysis that was her due, one that unpacked her astonishing voice, commanding stage presence, visual reproducibility, multiple personas, and unwavering fidelity to her music career. Despite her fame, I had to reconstruct the entire arc of her career from scratch. I had to carefully think this particular variation on the nothing, which brought so many items to analysis but was, in its richness, resistant to interpretation. Beyond my individual delight in working with recordings, interviewing people, and compiling a visual archive, I was able to witness up close and personal the secondary or nonexistent role women musicians, almost always singers, were assigned. Thinking about voice was often hard to come by in the case of women artists. My own position as a woman professor researching women singers for a scholarly book on gender and music was hard to communicate, difficult to recognize, indeed part of the nothing I had set out to study. My intention was to provide an analysis of women artists as having a concept, as not merely happening—just as with the perception of the voice as “merely happening,” to then be described, classified, measured, judged as success or failure, considered primarily in a social context, and so forth. I sought to theorize the voice in performance as having something to say, but not necessarily in a clear “message” way. Rather, the “nothing is something” manifests through voice’s fierce battle with freedom and subjugation. The object-voice is never only about one or the other, or about polarities of individual and social, private and public, self-expression and self-mystification, and so forth. I conceived of the thinking voice as an event, sometimes called forth consciously by a certain type of singer and sometimes appearing in a not so conscious or premeditated way; and I conceived of the women singers I study as harbingers of the nothing I responded to, which, however, does not imply a fixed, unchanging reality. Enter the five amazing scholars who graced the book with the comments reproduced in this issue, who surprised even me with elements they noticed, riffed on, and at times clarified: Arnaldo Cruz-Malavé, Gayatri Gopinath, Jack Halberstam, Fred Moten, and Alexandra Vazquez. These pieces were read at three New York City book events for The Great Woman Singer: Book Culture/Columbia University Center for Ethnomusicology, April 13th, 2017; New York University Center for the Humanities, October 17th, 2017; and the Center for Puerto Rican Studies, Hunter College, CUNY, December 12th, 2017. Heartfelt thanks to all in the venues for hosting us and to the audiences for tuning in to our feminist and critical listening. I would also like to thank Tom Wetmore and Current Musicology for their interest in this dossier. I am delighted these pieces are available to all interested readers, particularly scholars and students interested in questions of voice, gender, thought, and music. References Mowitt, John. 1987. “The Sound of Music in the Era of Its Reproducibility.” In Music and Society: The Politics of Composition, Performance, and Reception, edited by Richard Leppert and Susan McClary, 184–97. New York: Cambridge University Press